Segmentation of Bangla compound characters: underlying simple character detection from handwritten compound characters - Bhuiyan, Md Raihanul Islam; Efaz, Mahin Shahriar; Reza, Tanjim; Ria, Aditi Saha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.